Introduction - CIPOLLA, Maria Adele; QUINN, Judy (Brepols, 2016)
Short Introduction to the collection of essays by scholars from Italy, Sweden, Denmark, Norway, Germany, and the UK. They examine the scholarly and artistic reception of a variety of Old Norse texts from the twelfth-century Iceland to contemporary poetry, crime fiction, and graphic novels produced in Britain, Ireland, Italy, and Iceland.